THE ROLE OF LITERARY INFLUENCE IN THE CREATION AND ENRICHMENT OF THE KASHKADARIN TAJIK CEREMONIAL FOLKLORE - Shernazarov Akmal Andiyokulovich (Galaxy International Interdisciplinary Research Journal, 2021)
The article describes the role ofliterary influence in the creation and enrichment of the ritual folklore of the Tajiks of the Kashkadarya oasis, the nature and manifestation of Zullisonailin, the socio-psychological factors that led to this, their proximity, literary affiliation. interaction, bilingualism.